Group motivational interviewing in schools: Development of a health promotion intervention. (August 2016) - Hawkins, Jemma L; Bravo, Paulina; Gobat, Nina; Rollnick, Stephen; Jerzembek, Gabrielle; Whitehead, Sarah; Chanon, Sue; Kelson, Mark; Adams, Orla; Murphy, Simon
Objective: In the light of the shortcomings of curriculum-based health promotion in secondary schools, group motivational interviewing provides a potential alternative approach. This two-phase study set out to establish the key components, feasibility and acceptability of a group motivational interviewing intervention, focused on alcohol consumption. Methods: In phase 1, focus groups with 12 students and 8 teachers explored issues with existing health education in Wales. Phase 2 involved the development of a 1-hour group motivational interviewing session to address the issues raised. The session was delivered to two classes of students aged 13–15 years, facilitated by two motivational interviewing practitioners. Sessions were observed and audio-recorded and coded by two researchers using the Assessment of Motivational Interviewing Groups Observer Scale (AMIGOS). Student acceptability of the session was captured using a satisfaction questionnaire. Results: Sessions were consistent with motivational interviewing principles, providing empathic and focused discussion while maximising participants' autonomy and strengths. The majority of students felt listened to during the session, considered it was helpful and felt that they could learn more from this kind of experience. Conclusion: A group motivational interviewing session, developed based on key components identified during focus groups, was shown to be acceptable to students and feasible to deliver in secondary schools. The approach requires further research to establish sustainable delivery mechanisms.